Social-psychological features of new forms of adult education - Tamara Тkach (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The modern world is extremely acute problems of human development, regardless of age and status, and throughout her life. Inrecent years scientists have discovered that with age, intellectual abilities not only not weakened, but even improved. Therefore the older the topical problems of formation and development of own self, the ability to prove myself to myself and others, creating your own world, new forms of communication with others, things that have significance and value to a full human life. Thus, the motivation of adults to education in the twenty-first century have acquired a qualitatively new color.